Suicide prevention: Evaluation of a pilot intervention in a primary care context. (2013) - King, Kylie; Bassilios, Bridget; Reifels, Lennart; Fletcher, Justine; Ftanou, Maria; Blashki, Grant; Burgess, Philip; Pirkis, Jane
Abstract : Background: From July 2008 to June 2011, 19 Australian Divisions of General Practice piloted specialist services for consumers at risk of suicide within a broader primary mental health program. General practitioners and other mental health staff referred suicidal consumers to specially trained mental health professionals for intensive, time-limited care. Aims: To report the findings from an evaluation of the pilot. Method: Data sources included a purpose-designed minimum data set, which collated consumer-level and session-level data, and a series of structured telephone interviews conducted with Divisional project officers, referrers and mental health professionals. Results: There were 2312 referrals to the pilot; 2070 individuals took up the service. The pilot reached people who may not otherwise have had access to psychological care; over half of those who received services were on low incomes and about one-third had not previously accessed mental health care. Project officers, referrers and mental health professionals were all positive about the pilot and commented that it was meeting a previously unmet need. Consumers appeared to benefit, showing significant improvements in outcomes. Conclusion: This evaluation provides supportive evidence for the effectiveness of a suicide prevention intervention delivered by specially trained mental health professionals in a primary mental health environment.